Strategy and PowerPoint: An Inquiry into the Epistemic Culture and Machinery of Strategy Making - Kaplan, Sarah (Organization Science, 2011)
PowerPoint has come to dominate organizational life in general and strategy making in particular. The technology is lauded by its proponents as a powerful tool for communication and excoriated by its critics as dangerously simplifying. This study takes a deeper look into how PowerPoint is mobilized in strategy making through an ethnographic study inside one organization. It treats PowerPoint as a technology embedded in the discursive practices of strategic knowledge production and suggests that these practices make up the epistemic or knowledge culture of the organization. Conceptualizing culture as composed of practices foregrounds the “machineries” of knowing. Results from a genre analysis of PowerPoint use suggest that it should not be characterized simply as effective or ineffective, as current PowerPoint controversies do. Instead, I show how the affordances of PowerPoint enabled the difficult task of collaborating to negotiate meaning in an uncertain environment, creating spaces for discussion, making recombinations possible, allowing for adjustments as ideas evolved, and providing access to a wide range of actors. These affordances also facilitated cartographic efforts to draw boundaries around the scope of a strategy by certifying certain ideas and allowing document owners to include or exclude certain slides or participants. These discursive practices—collaboration and cartography—are part of the “epistemic machinery” of strategy culture. This analysis demonstrates that strategy making is not only about analysis of industry structure, competitive positioning, or resources, as assumed in content-based strategy research, but it is also about how the production and use of PowerPoint documents that shape these ideas.